A Co / TiO x Catalyst and its preparation method and application

By loading cobalt nanoparticles on the TiOx support, using the efficient light absorption and hydrogen overflow effects of low-valent titanium oxides, the problem of insufficient carbon dioxide conversion rate and activation capacity in existing photocatalytic technologies is solved, efficient photothermal catalytic carbon dioxide reduction is achieved, and production costs are reduced.

CN118949993BActive Publication Date: 2025-03-14FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411432877.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing photocatalytic technology has shortcomings in carbon dioxide conversion rate and activation capacity, and the preparation of catalysts in traditional impregnation methods is cumbersome and difficult to produce on a large scale.

Method used

Co/TiOx catalyst was used to load cobalt nanoparticles onto the TiOx support by rotary immersion-reduction method, and efficient carbon dioxide activation and hydrogenation were achieved by using the high-efficiency light absorption and hydrogen overflow effects of low-valent titanium oxides.

Benefits of technology

The reaction activity and selectivity of photothermal catalytic carbon dioxide reduction are significantly improved, efficient CO2 hydrogenation is achieved, and the amplified production of the catalyst is achieved through rotary immersion method, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949993B_ABST
    Figure CN118949993B_ABST
Patent Text Reader

Abstract

The present invention relates to a Co / TiO x Catalyst and its preparation method and application, the present invention belongs to the technical field of catalyst. x The catalyst is TiO x As a carrier, cobalt oxide nanoparticles were prepared by mixing with TiO x Strong carrier-metal interaction occurs for loading; the Co / TiO x There are unsaturated low-valent titanium atoms and hydroxyl groups on the catalyst surface; the TiO x Contains TiO, Ti2O3, Ti3O5 low-valent titanium oxide components. Compared with Co / TiO2 catalyst, Co / TiO x The reaction activity in the photothermal catalytic carbon dioxide reduction process has significant advantages. It is prepared by rotary distillation impregnation method, which can achieve scale-up production of catalysts at the level of 10 to 100 grams.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, in particular to a Co / TiO x Catalyst and its preparation method and application. Background Art

[0002] Photocatalytic technology has significant advantages over traditional thermal catalytic technology in terms of environmental friendliness, but currently photocatalytic technology is still limited by low conversion rates. This is because most traditional photocatalytic technologies have low utilization rates of light energy, and can usually only utilize the electron excitation effect of high-energy photons, but cannot effectively utilize the thermal effect of light, so that the reaction is usually carried out at room temperature, and the chemical reaction rate is proportional to the temperature. Therefore, the carbon dioxide conversion rate of traditional photocatalytic technology at low temperatures is low (micromolar level). On the other hand, carbon dioxide is a non-polar molecule with high chemical inertness, so it has weak interactions with many commonly used photocatalytic materials and cannot form effective adsorption and activation. Therefore, photocatalytic materials that lack efficient active sites will show extremely low activity due to their insufficient activation ability for carbon dioxide. Therefore, how to direct the design of the active sites of the catalyst to improve the catalyst's adsorption and activation ability for carbon dioxide molecules has become an important factor that needs to be considered in catalyst design.

[0003] 95% of the energy of sunlight is concentrated in the visible to infrared band, and ultraviolet light accounts for less than 5%. However, traditional semiconductor photocatalytic materials can only utilize ultraviolet light, and the utilization rate of visible light and near-infrared light is low, making the overall quantum efficiency extremely low. In order to improve the overall utilization rate of photocatalytic materials for solar energy, photocatalytic materials need to be modified. Among many modification methods, the construction of oxygen vacancies in metal oxides is an important modification method. In metal oxides, lattice oxygen can be dissociated under external physical or chemical effects, and the crystal defect sites formed are called oxygen vacancies. The generation of oxygen vacancies can construct a large number of geometric structural defects, and also expose a large number of low-valent coordinated unsaturated atoms around oxygen vacancies. These coordinated unsaturated atoms can effectively chemically adsorb carbon dioxide molecules and achieve efficient adsorption and activation of carbon dioxide. At the same time, oxygen vacancies can induce the generation of impurity energy levels, reduce the band gap width of metal oxides, and broaden their light absorption range. Taking the classic titanium dioxide photocatalytic material as an example, pure titanium dioxide is white, while TiO containing oxygen vacancies is white. 2-x It shows dark colors ranging from blue to black, and the Ti atoms at the oxygen vacancies are trivalent, which has a higher electron density than the tetravalent titanium in the complete TiO2 crystal, and can better adsorb and activate carbon dioxide molecules. However, for titanium dioxide, the number of oxygen vacancies that can be generated on its surface is always limited. No matter what modification method is used, its overall stoichiometric ratio is still close to Ti: O = 1:2, which makes the surface concentration of highly active unsaturated low-valent titanium insufficient.

[0004] Based on the above, a catalyst with a large number of low-valent coordinated unsaturated titanium atoms may have the ability of efficient light absorption and efficient carbon dioxide adsorption and activation, and has the potential for efficient photothermal catalytic carbon dioxide reduction.

[0005] In the prior art, cobalt is selected as the loaded metal type and TiO2 is used as the carrier. The traditional impregnation method usually uses a dropper to slowly add the metal salt solution to be impregnated in a container such as a porcelain boat, and then evaporates and removes the solvent by repeated stirring and mixing under infrared light. The operation is cumbersome, the mixing is not uniform, and it is difficult to carry out large-scale preparation.

[0006] In the prior art, metal cobalt nanoparticles loaded on the surface of a carrier can effectively activate hydrogen, so that hydrogen is cracked into hydrogen atoms, which can further migrate from the surface of the loaded metal cobalt nanoparticles to the surface of the carrier. This process is called hydrogen overflow. Although titanium monoxide has the potential to efficiently activate CO2, titanium oxide is not an excellent hydrogen activation center. Technicians use titanium monoxide as a carrier, load it with metal, and prepare loaded metal catalysts, which will hopefully solve the problem of low hydrogen activation efficiency. Hydrogen activation components commonly used in the prior art include precious metals, such as ruthenium, rhodium, palladium, etc., but their natural abundance is low and they are expensive.

[0007] In summary, the key issue in achieving efficient photocatalytic carbon dioxide reduction is to design a new type of photocatalytic material whose surface should have a strong adsorption and activation ability for carbon dioxide and can efficiently utilize solar energy to reach a suitable reaction temperature to drive the rapid conversion of carbon dioxide. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a Co / TiO x Catalyst and its preparation method and application. The present invention utilizes metal iron, cobalt, nickel, etc., which have hydrogen activation ability close to that of precious metals, but are low in price. Therefore, from the perspective of economic cost, they are more suitable for modifying titanium monoxide. Under the conditions of catalytic carbon dioxide hydrogenation reaction, the carrier TiO x The medium and low valent titanium oxide efficiently adsorbs and activates CO2, and realizes efficient light energy utilization through photothermal conversion. The loaded metal efficiently activates H2 and delivers protons to the adsorbed and activated CO2 molecules through the hydrogen overflow effect, thereby realizing efficient CO2 hydrogenation. x , which is expected to solve the shortcomings of vacancy-type catalysts constructed by defect engineering in high-valent metal oxides in carbon dioxide activation and photothermal conversion efficiency.

[0009] In the present invention, titanium monoxide TiO xIt is a black low-valent titanium oxide, which contains a large number of low-valent titanium atoms (such as Ti2O3, Ti3O5, TiO). Compared with titanium dioxide, due to TiO x The color is black, so in the photocatalytic process, titanium monoxide TiO x The material can not only effectively utilize ultraviolet-visible light, but also near-infrared light. It can generate a local thermal field through photothermal conversion efficiency, making the temperature of the catalyst surface much higher than that of traditional photocatalytic materials under the same lighting conditions. The local thermal field generated by photothermal conversion can effectively increase the chemical reaction rate of the interface and promote the progress of photothermal catalytic reactions. At the same time, titanium monoxide TiO x There are a lot of low-valent titanium atoms in the titanium dioxide, and its electronic structure is very similar to the low-valent titanium atoms in the oxygen vacancies of titanium dioxide, but titanium monoxide TiO x The concentration of low-valent titanium in the TiO is much higher than that in TiO produced by vacancy engineering. 2-x The concentration of low-valent titanium in the titanium monoxide TiO x Surfaces can become more efficient carbon dioxide activation centers.

[0010] The first object of the present invention is to provide a Co / TiO x Catalyst, the Co / TiO x The catalyst is TiO x As a carrier, cobalt oxide nanoparticles were prepared by mixing with TiO x Strong carrier-metal interactions occur for loading;

[0011] The Co / TiO x There are coordination-unsaturated low-valent titanium atoms and hydroxyl groups on the catalyst surface;

[0012] The TiO x Contains low-valent titanium oxide components such as TiO, Ti2O3 and Ti3O5.

[0013] In some embodiments of the present invention, the loading amount of the cobalt nanoparticles is 0.1wt% to 3wt%. For example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, etc., or any interval value between any two values, such as 0.1wt% to 0.5wt%, 0.5wt% to 3wt%, 0.5wt% to 1wt%, 1wt% to 3wt%, etc.

[0014] In the present invention, the support material TiO x Contains a variety of low-valent titanium oxide components such as TiO, Ti2O3, and Ti3O5. The electronic structure of the Ti atoms in these low-valent titanium oxides has a higher electron density. Compared with the tetravalent titanium in traditional TiO2, low-valent titanium can better adsorb and activate CO2 molecules.

[0015] The second object of the present invention is to provide the Co / TiO x The method for preparing a catalyst comprises the following steps:

[0016] Providing a TiO x powder;

[0017] The cobalt source is dissolved in an organic solvent and TiO x powder, and mixing by ultrasonic stirring to obtain a suspension;

[0018] The suspension was stirred continuously, and then transferred to a rotary evaporator to remove the organic solvent to obtain a TiO2 uniformly impregnated with the cobalt source. x powder;

[0019] The obtained TiO impregnated with cobalt source was heated under a reducing atmosphere. x The powder undergoes a reduction reaction under heating conditions to obtain the Co / TiO x catalyst.

[0020] The present invention adopts ball-milled bulk commercial titanium monoxide as a carrier and prepares Co / TiO2 loaded with cobalt nanoparticles by rotary evaporation impregnation-reduction method. x catalyst.

[0021] In some embodiments of the present invention, the organic solvent is selected from ethanol and / or methanol.

[0022] In some embodiments of the present invention, the cobalt source is selected from one or more of cobalt nitrate, cobalt acetate, and cobalt oxalate.

[0023] In some embodiments of the present invention, the cobalt source and TiO x The mass ratio of the powder is 0.15:3~0.20:3.

[0024] In some embodiments of the present invention, the suspension is stirred for 2 to 5 hours.

[0025] In some embodiments of the present invention, the heating condition has a temperature of 150-230° C. and a time of 2-5 h;

[0026] During heating, a tube furnace is used for heating or a xenon lamp is used for irradiation to achieve photothermal effect.

[0027] The reaction reaches the required temperature by utilizing the photothermal effect stimulated by xenon lamp irradiation, and the temperature control can adjust the power of the xenon lamp;

[0028] The reducing atmosphere is a hydrogen atmosphere.

[0029] In some embodiments of the present invention, the wavelength of the light source in the xenon lamp illumination is 300-2500 nm.

[0030] The third object of the present invention is to provide the Co / TiO x Application of catalysts in the photothermal catalytic reduction of carbon dioxide to carbon monoxide.

[0031] The above technical solution of the present invention has the following advantages compared with the prior art:

[0032] (1) The cobalt nanoparticles loaded in the present invention can react with TiO x A strong support-metal interaction occurs, and the CO2 adsorbed on the low-valent titanium sites is hydrogenated by the hydrogen overflow effect, resulting in almost 100% selective photothermal reduction of CO2 to CO. Compared with the traditional Co / TiO2 catalyst, Co / TiO x The reaction activity in the photothermal catalytic carbon dioxide reduction process has significant advantages.

[0033] (2) The rotary distillation impregnation method can be used to achieve gram-scale production of the catalyst.

[0034] (3) The commonly used high-activity photothermal carbon dioxide reduction Ru / TiO2 catalyst was selected as a comparison object, and Co / TiO xThe cost of synthetic reagents is much lower than that of Ru / TiO2. The specific comparison results are as follows: (1) The price of commercial reagent (1440 yuan / 500 g) of non-nanomaterial carrier part titanium monoxide (CAS: 12137-20-1) is 1 / 10 of the price of commercial high-activity P25 titanium dioxide (CAS: 13463-67-7) (2576 yuan / 100 g). (2) The earth's occurrence of cobalt used in the present invention is about 50,000 times that of ruthenium, and its price is 2.8% of ruthenium. Therefore, the present invention has outstanding advantages in terms of economic cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0036] Figure 1 The morphological changes of the catalysts before and after preparation and reduction, especially the surface-modified cobalt;

[0037] Figure 2 (a) is Co / TiO x O 1s XPS results of (b) Co / TiO x Ti 2p XPS results; (c) Co / TiO x High-resolution transmission electron microscopy image; (d) Co / TiO x Co 2p XPS results; (e) Co / TiO x XRD of Co / TiO x High-resolution transmission electron microscopy TEM image;

[0038] Figure 3 The Co / TiO obtained in Example 1 of the present invention x Electron energy loss spectra and element distribution diagram of Ti at different positions on the catalyst;

[0039] Figure 4 Co / TiO x Electron energy loss spectra of Ti and Co at different Co loading positions;

[0040] Figure 5 The catalyst prepared in large quantities in Example 1;

[0041] Figure 6 (a) Co / TiO with different cobalt loadings x Catalyst activity; (b) Photothermal catalytic CO2 reduction activity of different samples; (c) Co / TiO x Stability test of photothermal catalytic CO2 reduction. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] Experimental instruments and drugs used in the present invention

[0044] Table 1 Main experimental drugs

[0045]

[0046] Table 2 Main experimental instruments

[0047]

[0048] Example 1

[0049] This embodiment provides a Co / TiO x The preparation method of the catalyst is as follows:

[0050] (1) Convert non-nanomaterial commercial reagent titanium monoxide TiO x The blocky titanium monoxide was ground into TiO using a ball mill. x powder.

[0051] (2) Dissolve 0.18 g of cobalt nitrate hexahydrate in 40 mL of anhydrous ethanol. After the cobalt nitrate is completely dissolved, add 3 g of TiO x The powder was stirred and mixed under ultrasound to obtain a uniform suspension.

[0052] (3) The suspension in step (2) was stirred for 4 h using a magnetic stirrer, and then the suspension was transferred to a rotary evaporator to remove the ethanol solvent to obtain a TiO2 uniformly impregnated with cobalt nitrate. x powder.

[0053] (4) The TiO2 impregnated with cobalt nitrate obtained in step (3) is x The powder was reduced in a hydrogen tube furnace at 200 °C for 4 h to obtain the final Co / TiO x Catalyst. The obtained Co / TiO x The catalyst was characterized and analyzed for its structure. Figure 1-4 .

[0054] right Figure 1 The catalyst was characterized by ICP-MS, and the results showed that the Co / TiO x The cobalt content of the catalyst is 1.2wt%. xThe structural characteristics of the catalyst were detected by scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS-Mapping). Figure 1 The sample after preparation and reduction can be seen in the TiO x A large number of bright spots appeared on the surface. This is because the relative atomic mass of cobalt is greater than that of Ti and O, so it presents a higher z contrast in STEM characterization, indicating the successful loading of cobalt nanoparticles. EDS-mapping results further characterized the element distribution on the catalyst surface. Good overlap of O, Ti and Co elements can be observed, indicating that cobalt nanoparticles are uniformly loaded on TiO x To further detect the composition of the catalyst, the catalyst was characterized by X-ray photoelectron spectroscopy (XPS). XPS was tested using an X-ray photoelectron spectrometer (model ESCALAB250Xi) from Thermo Fisher Scientific, USA, and the binding energy C of the background carbon was used as the 1s = 284.60 eV as the standard for charge correction. The results are shown in Figure 2 In (a)-(d), it can be seen from the figure that Co / TiO x The O1s spectrum of Co / TiO shows a signal attributable to Ti-O lattice oxygen, and also shows a large number of signals attributable to molecular oxygen adsorbed at oxygen vacancies, indicating that the x There are a large number of unsaturated low-valent titanium atoms in the O1s XPS. A small amount of OH signals also appeared in the O1s XPS, which may be due to the hydrogen reduction process of Co / TiO x A small amount of surface hydroxyl groups are generated on the surface. Co / TiO x A large number of characteristic peaks belonging to low-valent titanium species appeared in the Ti2p XPS spectrum, including TiO, Ti2O3, and Ti3O5, indicating that the titanium monoxide carrier TiO x The chemical composition of TiO is relatively complex, and its stoichiometric ratio is not strictly Ti:O=1:1, but is composed of a large number of complex low-valent titanium oxides. x Mixed phase (Ti2O3, Ti3O5, TiO). Co / TiO x The Co 2pXPS spectrum shows that cobalt mainly appears in the form of divalent oxide CoO, indicating that the loaded Co nanoparticles are likely to be x A strong carrier-metal interaction occurs, making the cobalt nanoparticles present an oxide valence state. XPS characterization results further prove that the carrier TiO x The presence of medium and low-valent titanium and cobalt loaded on the support surface indicates the successful preparation of the catalyst. Figure 2 (e) further supports the conclusion that Co / TiO xThe main crystal phase components of the catalyst carrier are TiO, Ti2O3 and Ti3O5. Figure 2 (c) and (f) also show the high-resolution ordered structure of the catalyst.

[0055] Depend on Figure 3 It can be concluded that Co / TiO x TiO on catalyst x The carrier is composed of a variety of low-valent titanium oxides, which shows the diversity of low-valent Ti. x The electron energy loss spectra of Ti at different sites on the catalyst illustrate the diversity of Ti valence states in the catalyst support TiOx.

[0056] Depend on Figure 4 It can be concluded that Co / TiO x The Co on the catalyst is CoO, but its fine structure is slightly different. Ti1-Ti3 in the figure are the electron energy loss spectra of Ti at the position of CoO.

[0057] Example 2

[0058] Similar to Example 1, the difference is that in step (2), 0.015 g of cobalt nitrate hexahydrate is dissolved in 40 mL of anhydrous ethanol, and after the cobalt nitrate is completely dissolved, 3 g of TiO x The powder was stirred and mixed under ultrasound to obtain a uniform suspension. The final Co / TiO x The cobalt content of the catalyst was 0.1 wt%.

[0059] Example 3

[0060] Similar to Example 1, the difference is that in step (2), 0.075 g of cobalt nitrate hexahydrate is dissolved in 40 mL of anhydrous ethanol, and after the cobalt nitrate is completely dissolved, 3 g of TiO x The powder was stirred and mixed under ultrasound to obtain a uniform suspension. The final Co / TiO x The cobalt content of the catalyst was 0.5 wt%.

[0061] Example 4

[0062] Similar to Example 1, the difference is that in step (2), 0.15 g of cobalt nitrate hexahydrate is dissolved in 40 mL of anhydrous ethanol, and after the cobalt nitrate is completely dissolved, 3 g of TiO x The powder was stirred and mixed under ultrasound to obtain a uniform suspension. The final Co / TiO x The cobalt content of the catalyst was 1 wt%.

[0063] Example 5

[0064] Similar to Example 1, the difference is that in step (2), 0.45 g of cobalt nitrate hexahydrate is dissolved in 40 mL of anhydrous ethanol, and after the cobalt nitrate is completely dissolved, 3 g of TiO x The powder was stirred and mixed under ultrasound to obtain a uniform suspension. The final Co / TiO x The cobalt content of the catalyst was 3 wt%.

[0065] Comparative Example 1

[0066] This comparative example provides a preparation method and application of a Co / TiO2 catalyst, which are as follows:

[0067] Similar to Example 1, the difference is that in step (1), TiO x The powder was replaced with TiO2 powder to finally obtain Co / TiO2 catalyst.

[0068] Application performance:

[0069] The Co / TiO x Catalyst and Co / TiO2 catalyst obtained in Comparative Example 1, as well as TiO2 (purchased from Sinopharm Chemical Reagent Co., Ltd.), TiO x The photothermal activity evaluation of (purchased from Aladdin) was carried out under the reaction conditions of a carbon dioxide and hydrogen volume ratio of 1:1, as follows:

[0070] 0.05 g Co / TiO x The catalyst is evenly dispersed in a quartz reactor. Argon is first introduced into the reactor to fully replace the air. After 10 minutes, the argon flow is stopped and carbon dioxide and hydrogen are introduced. The flow rate of carbon dioxide and hydrogen is 5 mL / min, and the gas flow rate is controlled by an electronic flowmeter. Ten minutes after the introduction of carbon dioxide and hydrogen, the atmosphere in the reactor has stabilized. The xenon lamp light source with a wavelength of 300-2500 nm is turned on to start the reaction. At this time, the surface of the catalyst begins to heat up. The surface temperature of the catalyst is monitored by a thermocouple, and the temperature can be controlled by adjusting the output power of the xenon lamp. After the temperature is stabilized at 280°C for 10 minutes, the type and concentration of each component in the product gas are detected by online gas chromatography. The gas chromatograph uses an FID detector and nitrogen as the carrier gas (Note: Since pure titanium dioxide is a white powder and does not have the ability of photothermal conversion, when testing pure titanium dioxide, an additional electric heating plate will be added as a heat source so that its surface temperature also reaches 280°C). The experimental results are shown in Figure 6 .

[0071] Figure 6 (a) shows Co / TiO with different cobalt loadings xThe catalytic activity of the catalyst shows that as the cobalt loading increases from 0.1wt% to 0.5wt% and then to 1wt%, the activity of the catalyst increases significantly. This is because cobalt is the hydrogen activation center in the catalyst, and the increase in content increases the hydrogen activation center. However, as the cobalt loading increases from 1wt% to 3wt%, the activity of the catalyst only increases by less than 15% (6.2 mmol / g / h to 7.1 mmol / g / h). Therefore, the Co / TiO x The photothermal catalytic activity of different samples at 280 °C was then tested. Figure 6 As shown in (b), Co / TiO x The catalyst has the highest carbon monoxide production rate (6.3mmol CO / g / h) and selectivity (>98%) at 280℃, and the Co / TiO x The catalytic activity of the catalyst is 5 times that of the Co / TiO2 catalyst obtained in Comparative Example 1, indicating that the TiO x The carrier has stronger CO2 activation ability than the TiO2 carrier. x Support, Co / TiO x The activity of Co / TiO was also increased by 37 times, indicating that the loading of cobalt effectively improved the activity of the catalyst. This is because cobalt is an efficient hydrogen activation center, and the loading of cobalt significantly increases the hydrogenation rate of adsorbed CO2. To test the stability of the catalyst, Co / TiO x The catalyst was cycled and the results were as follows Figure 6 As shown in (c): It can be seen that the activity and selectivity of the catalyst did not decrease significantly within 36 h, indicating that the catalyst has excellent chemical stability under photothermal conditions.

[0072] Economical:

[0073] In order to further evaluate the economic feasibility of this method, cost accounting was performed. At present, a large number of photothermal catalytic carbon dioxide reduction catalysts use precious metal loading modification strategies, such as Ru, Pt, etc. The carrier used in the present invention is titanium monoxide, and titanium dioxide is used as a control. Therefore, cost accounting can be divided into two parts, the carrier cost and the loaded metal cost. At present, the price of commercial high-activity P25 titanium dioxide (CAS: 13463-67-7) is 2576 rmb / 100 g, and titanium monoxide (CAS: 12137-20-1) is relatively cheap as a commercial reagent because it is not a nanomaterial, which is 1440 rmb / 500 g. Its gram price is much lower than that of the nanomaterial P25 titanium dioxide. On the other hand, taking the most widely used ruthenium-based catalyst as an example, when the loading ratio is also 1% by mass, the activity of Ru / TiO2 is exactly that of Co / TiOx The conversion rate of ruthenium is about twice that of cobalt, and its conversion rate reaches the equilibrium limit at 280 ° C, but ruthenium is one of the rarest elements in the earth's crust, and its abundance in the earth (0.0004 ppm) is much lower than that of cobalt (0.002%). Therefore, even though the cobalt content in my country is not abundant, the price of commercial cobalt-containing reagents is much lower than that of ruthenium-containing reagents. Considering that the present invention uses the impregnation method as a means of catalyst synthesis, the price of the metal precursor used should also be used as an important factor for cost accounting. Two common precursors of ruthenium used for the synthesis of catalysts by impregnation method are ruthenium chloride (CAS: 14898-67-0) and ruthenium dodecacarbonyl (CAS: 15243-33-1), whose market prices are 699 RMB / g and 1199 RMB / g respectively, while the price of cobalt nitrate (CAS: 10026-22-9) is only 176 RMB / 500 g. Therefore, it can be calculated that the price of Ru / TiO2 per gram (using ruthenium dodecacarbonyl as precursor) is 101 RMB, while the price of Co / TiO2 per gram is 101 RMB. x The price is only 2.8 yuan, which is less than 3% of the precious metal catalyst's overall price. By optimizing the CO2 activation ability of the carrier alone, the cheap metal-loaded catalyst has achieved 50% of the reaction efficiency of the precious metal catalyst. Therefore, this work is superior in terms of economic cost.

[0074] In summary, the present invention uses ball-milled bulk commercial titanium monoxide as a carrier and prepares Co / TiO2 loaded with cobalt nanoparticles by rotary evaporation impregnation-reduction method. x Catalyst. In this catalyst, the support material TiO x It contains a variety of low-valent titanium oxide components such as TiO, Ti2O3, and Ti3O5. The electronic structure of the Ti atoms in these low-valent titanium oxides has a higher electron density. Compared with the tetravalent titanium in traditional TiO2, low-valent titanium can better adsorb and activate CO2 molecules. At the same time, the loaded cobalt nanoparticles can bind to TiO x A strong support-metal interaction occurs, and the CO2 adsorbed on the low-valent titanium sites is hydrogenated by the hydrogen overflow effect, resulting in the photothermal reduction of CO2 to CO with almost 100% selectivity. x The catalyst has significant advantages in the reactivity of photothermal catalytic carbon dioxide reduction. At the same time, the catalyst can be scaled up to produce grams through rotary distillation impregnation.

[0075] The commonly used high-activity photothermal carbon dioxide reduction Ru / TiO2 catalyst was selected as the comparison object, and Co / TiO xThe cost of synthetic reagents is much lower than that of Ru / TiO2. The specific comparison results are as follows: the price of the commercial reagent (1440 rmb / 500 g) of the non-nanomaterial carrier part titanium monoxide (CAS: 12137-20-1) is 1 / 10 of the price of the commercial high-activity P25 titanium dioxide (CAS: 13463-67-7) (2576 rmb / 100 g); the earth's occurrence of cobalt used in this study is about 50,000 times that of ruthenium, and the price is 2.8% of ruthenium. Therefore, the present invention has outstanding advantages in terms of economic cost.

[0076] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A Co / TiO x A catalyst, characterized in that The Co / TiO x The catalyst is TiO x As a carrier, cobalt oxide nanoparticles were prepared by mixing with TiO x Strong carrier-metal interactions occur for loading; The Co / TiO x There are coordination-unsaturated low-valent titanium atoms and hydroxyl groups on the catalyst surface; The TiO x Contains TiO, Ti2O3, Ti3O5 low-valent titanium oxide components; The Co / TiO x The preparation method of the catalyst comprises the following steps: Providing a TiO x powder; The cobalt source is dissolved in an organic solvent and TiO x powder, and mixing by ultrasonic stirring to obtain a suspension; The suspension was stirred continuously, and then transferred to a rotary evaporator to remove the organic solvent to obtain a TiO2 uniformly impregnated with the cobalt source. x powder; The obtained TiO impregnated with cobalt source was heated under a reducing atmosphere. x The powder undergoes a reduction reaction under heating conditions to obtain the Co / TiO x Catalyst; the loading amount of the cobalt oxide nanoparticles is 0.1wt%~3wt%.

2. Co / TiO according to claim 1 x A catalyst, characterized in that The organic solvent is selected from ethanol or methanol.

3. Co / TiO according to claim 1 x A catalyst, characterized in that The cobalt source is selected from one or more of cobalt nitrate, cobalt acetate and cobalt oxalate.

4. Co / TiO according to claim 1 x A catalyst, characterized in that The cobalt source and TiO x The mass ratio of the powder is 0.15:3~0.20:

3.

5. Co / TiO according to claim 1 x A catalyst, characterized in that The suspension is stirred for 2 to 5 hours.

6. Co / TiO according to claim 1 x A catalyst, characterized in that The heating condition is a temperature of 150-230°C and a time of 2-5 hours; When heating, use tube furnace heating or xenon lamp irradiation to achieve photothermal effect; The reducing atmosphere is a hydrogen atmosphere.

7. Co / TiO according to claim 6 x A catalyst, characterized in that The wavelength of the light source in xenon lamp illumination is 300-2500 nm.

8. Use of the Co / TiOx catalyst according to any one of claims 1 to 7 in the photothermal catalytic reduction of carbon dioxide to carbon monoxide.

Citation Information

Patent Citations

  • Cobalt-based catalyst for low-temperature carbon dioxide hydrogenation methanation reaction and preparation method thereof

    CN118287098A

  • Catalyst Pt / TiN, preparation method thereof and application of catalyst Pt / TiN in photocatalytic reduction of carbon dioxide to carbon monoxide

    CN118341469A